Appropriate technology application of traditional clove oil production, effort to up-grade quality - Musthofa Lutfi; Kusubakti Andjani; Ilhamuddin Ilhamuddin; Hamidah Nayati Utami; Firdiani Nur Afifah (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2020)
In East Java, the production of clove leaf oil refinement is developed by businesses owned by rural people. The processing operation is simple and start-up investment is low. The clove leaf oil manufacturing procedure uses old leaves that fall naturally in the dry season, these are found to be better preserved, mature and environmentally friendly. East Java rural distillers use a single boiler for steam, water and raw materials in order for the investment costs to remain low. This study aimed to research the use of appropriate technology for the clove leaf distillation process and how to increase clove oil both in yield and quality. Two different tests were conducted; introducing a leaf crusher as a raw material and replace the old chamber material with stainless steel. There are three grades of raw materials; rough leaves, smooth leaves, and non-crushed leaves. After the clove leaves were crushed, they are distilled in the new stainless steel boiler with an aim to compare the oil yield and quality. The result from the crushed leaves treatment indicates there are different volume condensates produced from the same volume of raw materials, 128.2 litres from smooth grade and 117.2 litres from rough grade leaves. The highest percentage of clove oil (15.07%) results from rough grade crushed leaves. By replacing the chamber material with stainless steel positively affects the brightness of the clove oil. In conclusion, these two tests, to improve appropriate technology for clove oil production, can increase both yield and oil brightness, and subsequently improve the competitive advantage and future aspiration of the product.